2014
DOI: 10.3109/15360288.2014.911237
|View full text |Cite
|
Sign up to set email alerts
|

Pain and Treatment From a Human Primate Perspective

Abstract: Human animals have evolved with the primary missions of survival and reproduction and these natural drives may impact behavior whether humans are aware of them or not. The author offers evidence in support of the idea that injury and resulting acute or chronic pain may trigger the unconscious human primate brain to believe there is a threat to survival. This perceived threat may be exacerbated or mitigated by the pain manager, both of which may impact health outcomes in a negative or positive way, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…Moreover, in our study, the anesthetist came to the patient five to ten minutes after the patient arrived on the operating ward. Pain inflicted by healthcare professionals might provoke anxiety, and in our unconscious mind, pain might be linked to threat and danger [36]. Research on patients' experiences of dialogues prior to, during and after surgery with the same nurse, however, revealed that patients considered the talks they had and the continuity to be anxiety-reducing [37] [38] and even that they "prevented and alleviated suffering in surgical procedures" [37].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in our study, the anesthetist came to the patient five to ten minutes after the patient arrived on the operating ward. Pain inflicted by healthcare professionals might provoke anxiety, and in our unconscious mind, pain might be linked to threat and danger [36]. Research on patients' experiences of dialogues prior to, during and after surgery with the same nurse, however, revealed that patients considered the talks they had and the continuity to be anxiety-reducing [37] [38] and even that they "prevented and alleviated suffering in surgical procedures" [37].…”
Section: Discussionmentioning
confidence: 99%